Analyser les réseaux du passé en archéologie et en histoire - Anna Collar (Les Nouvelles de l’Archéologie, 2014)
The last decade has seen a significant increase in the use of network studies in archaeology, as archaeologists have turned to formal network methods to make sense of large and complex datasets and to explore hypotheses of past interactions. A similar pattern can be seen in history and related disciplines, where work has focused on exploring the structure of textual sources and analysing historically attested social networks. Despite this shared interest in network approaches and their common general goal (to understand human behaviour in the past), there has been little cross-fertilisation of archaeological and historical network approaches. The Connected Past, a multidisciplinary conference held in Southampton in March 2012, provided a rare platform for such cross-disciplinary communication. This article will discuss the shared concerns of and seemingly unique challenges facing archaeologists and historians using network analysis techniques, and will suggest new ways in which research in both disciplines can be enhanced by drawing on the experiences of different research traditions. The conference brought some common themes and shared concerns to the fore. Most prominent among these are possible methods for dealing with the fragmentary nature of our sources, techniques for visualising and analysing past networks - especially when they include both spatial and temporal dimensions - and interpretation of network analysis results in order to enhance our understanding of past social interactions. This multi-disciplinary discussion also raised some fundamental differences between disciplines: in archaeology, individuals are typically identified indirectly through the material remains they leave behind, providing an insight into long-term changes in the everyday lives of past peoples; in contrast, historical sources often allow the identification of past individuals by name and role, allowing synchronic analysis of social networks at a particular moment in time. The conference also demonstrated clearly that a major concern for advancing the use of network analysis in both the archaeological and historical disciplines will be the consideration of how to translate sociological concepts that have been created to deal with interaction between people when the nodes in our networks are in fact words, texts, places or artefacts. Means of textual and material critique will thus be central to future work in this field.